The Status and Prospects of Epigenetics in the Treatment of Lymphoma - Liu, Jiaxin; Li, Jia-nan; Wu, Hongyu; Liu, Panpan (Frontiers in Oncology, 2022)
The regulation of gene transcription by epigenetic modifications is closely related to many important life processes and is a hot research topic in the post-genomic era. Since the emergence of international epigenetic research in the 1990s, scientists have identified a variety of chromatin-modifying enzymes and recognition factors, and have systematically investigated their three-dimensional structures, substrate specificity, and mechanisms of enzyme activity regulation. Studies of the human tumor genome have revealed the close association of epigenetic factors with various malignancies, and we have focused more on mutations in epigenetically related regulatory enzymes and regulatory recognition factors in lymphomas. A number of studies have shown that epigenetic alterations are indeed widespread in the development and progression of lymphoma and understanding these mechanisms can help guide clinical efforts. In contrast to chemotherapy which induces cytotoxicity, epigenetic therapy has the potential to affect multiple cellular processes simultaneously, by reprogramming cells to achieve a therapeutic effect in lymphoma. Epigenetic monotherapy has shown promising results in previous clinical trials, and several epigenetic agents have been approved for use in the treatment of lymphoma. In addition, epigenetic therapies in combination with chemotherapy and/or immunotherapy have been used in various clinical trials. In this review, we present several important epigenetic modalities of regulation associated with lymphoma, summarise the corresponding epigenetic drugs in lymphoma, and look at the future of epigenetic therapies in lymphoma.